2021
DOI: 10.1136/bmjopen-2021-049369
|View full text |Cite
|
Sign up to set email alerts
|

Intention to have the seasonal influenza vaccination during the COVID-19 pandemic among eligible adults in the UK: a cross-sectional survey

Abstract: ObjectiveTo investigate the likelihood of having the seasonal influenza vaccination during the COVID-19 pandemic in individuals who were eligible to receive it.DesignWe conducted a cross-sectional online survey in July 2020. We included predictors informed by previous research, in the following categories: sociodemographic variables; uptake of influenza vaccine last winter and beliefs about vaccination.Participants570 participants (mean age: 53.07; 56.3% female, 87.0% white) who were eligible for the free seas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…Previous vaccination behavior, favorable attitudes toward vaccination, perceived benefits from vaccination, trust in authorities associated with vaccine approval, perceived regret from not having accepted the vaccine and infecting others, as well as the belief that significant others around them expect them to accept a COVID-19 and influenza vaccine were identified as factors predicting vaccination intention for both vaccines. These findings are in line with similar research on vaccine intention for influenza 27 , 45 , 65 and for COVID-19. 34 , 59 , 66 , 67 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Previous vaccination behavior, favorable attitudes toward vaccination, perceived benefits from vaccination, trust in authorities associated with vaccine approval, perceived regret from not having accepted the vaccine and infecting others, as well as the belief that significant others around them expect them to accept a COVID-19 and influenza vaccine were identified as factors predicting vaccination intention for both vaccines. These findings are in line with similar research on vaccine intention for influenza 27 , 45 , 65 and for COVID-19. 34 , 59 , 66 , 67 …”
Section: Discussionsupporting
confidence: 92%
“…Other studies have also found concerns about adverse effects and vaccine novelty to be associated with COVID-19 vaccination intention. 45 , 53 Area deprivation as a predictor of intention aligns with previous work showing lower levels of actual vaccination in more deprived areas, 54 , 55 which has been linked to lower levels of trust in government and public health authorities. 55 In our analysis, socio-economic status and trust were both independently associated with vaccination intention, suggesting that the influence of socio-economic status extends beyond its association with trust.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In line with previous evidence ( 28 , 29 ), vaccination history in former seasons is conducive to future seasons. This hints to administrative departments to take action before it is too late.…”
Section: Discussionsupporting
confidence: 91%